Entrapment of vaginal ring pessary: A Case report and review of the literature - Zeelha Abdool (South African Medical Association, 2015)
The use of vaginal pessaries for symptomatic pelvic organ prolapse (POP) is well established. Recently pessaries have been offered routinely as a first-line treatment option for symptomatic POP, and in patients with medical comorbidity, those who are unfit for surgical intervention, and young women who still wish to bear children. The favourable physical and chemical properties of silicone have made pessaries safer to use for the treatment of POP. Complications associated with neglected pessaries are well documented, and it is probable that complications are rare when pessary care is regular. We present a case of partial encapsulation of a ring pessary despite regular follow-up at a tertiary urogynaecological unit, and review the literature pertaining to early entrapment of vaginal ring pessaries.